A didactic approach to develop professional skills in Elementary Physiology for Nursing students in Cienfuegos Medical School. - Leyla Georgina Pérez Piñeiro; José Carlos Pérez González; Juan Antonio Castellanos Álvarez (Medisur)
Background: The present days demand a turn in the nursing formation process in the medical university which may satisfy the requirement of the present times. Objectives: to design a didactical proposal to educate the professional abilities in Basic Physiology for nursing students. Methods: a descriptive study with a universe of 117 nursing students from 3rd to 5th academic year who have already received Physiology; graduated students from academic year 1998 to 2003 who were actively working in health facilities in the province . 100% of professors from the physiology department and the nursing department who woked in the basic cycle were also part of the universe. The expertise selection was carried out according to the educational category, scientific category, more than 25 years of experience teaching this subject. Results: Students as well as professor consider that the contents received in this subject are not enough for their future job with the patient. The main difficulty identified in the students is the ability formation from this subject which responds to the final objectives of the nursing student.